Świeccy fundatorzy instytucji dobroczynnych w Kościele starożytnym - Wójcik, Monika (Vox Patrum, 2003)
Charitable activities go back to the very beginning of Christianity, but charity institutions were founded since the fourth century. In 321 A.D. the Church was granted testament factio passiva which allowed lay people to cede their property to the Church. In many cases there is no certainty about who the founder of a charity was. However, it is certain that the first founders were bishops. The earliest information about lay founders date back to the first half of the fourth century in the East and the end of the fourth century in the West. The historical sources of the following centuries are more numerous. Also, imperial constitutions, many of which were issued by Justinian, were the proof of charities founded by lay people and they functioned as a safeguard of the instructions concerning charitable activities. Lay founders were given a legal guarantee to run the charity they founded. However, the legal status of the charitable institutions of that time is still a matter of argument.